THE FUNCTIONALIZATION OF THE USE OF ENGLISH IN COMMUNITY SOCIAL INTERACTION IN TOURISM AREAS IN SIMALUNGU REGENCY - Tauhid, Booni (Akademi Pariwisata Darma Agung, 2022)
The purpose of this research is to find out how the use of English which is an international language, especially in the tourism area in community social interaction, supports and inhibits the use of English in the social interactions of people in tourism areas in Simalungun Regency. The research method used is a qualitative research method where the technique used is to prioritize interview and documentation techniques. The results of this study are also a justification where interaction in English in the community can support the development and potential of tourism in the tourism area in Simalungun Regency is still very minimal. The use of English is only mastered mostly by a tour guide or tour guide in a tourism area. In addition, the inhibiting factor is the lack of interest in learning English and the low human resources of some people in the tourism area in Simalungun Regency.